The Feldstein-Horioka Paradox – evidence for Colombia during 1925-2011 (2015)
This paper examines the relationship between national investment and saving in Colombia during the period 1925-2011 -- Consistent with Cardenas and Escobar (1998), an Error Correction Model is used to examine short and long run effects -- The results provide evidence that investment and saving are co-integrated during the study period -- The results for the co-integration vector, with and without structural breaks, indicate that capital mobility was low, which is consistent with the Feldstein – Horioka [1980] paradox -- The results imply that increases in domestic saving rates reduce the mobility of financial capital in Colombia